2016
DOI: 10.1037/rmh0000058
|View full text |Cite
|
Sign up to set email alerts
|

The successes of experienced rural counselor supervisors and their recommendations for rural mental health.

Abstract: In this phenomenological study, rural counselor supervisors (N ϭ 11) describe their beliefs about their success and their ideas to improve rural mental health. Each participant had over 15 years of experience as counselors and over 10 years of experience as supervisors in rural settings. Success was individually defined by each participant. Using Auerbach and Silverstein's ( 2003) qualitative data analysis method, 6 overarching themes emerged regarding their beliefs about their success as counselors and superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Feedback from participants also suggested considering a hybrid program that might include in-person booster sessions for skills practice. Researchers have demonstrated that community connections and trust are important factors in building relationships with mental health providers in rural settings (McNichols et al, 2016). Therefore, in addition to translating booster sessions to a technology-based format, it may also be important to provide an in-person format so that school personnel can select the delivery modality that is best suited for the needs of their school.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback from participants also suggested considering a hybrid program that might include in-person booster sessions for skills practice. Researchers have demonstrated that community connections and trust are important factors in building relationships with mental health providers in rural settings (McNichols et al, 2016). Therefore, in addition to translating booster sessions to a technology-based format, it may also be important to provide an in-person format so that school personnel can select the delivery modality that is best suited for the needs of their school.…”
Section: Discussionmentioning
confidence: 99%
“…In the second half, we show how domestic violence center staff are key, albeit ad hoc, providers of mental health services to women experiencing IPV—as well as under- or unrecognized authorities in mitigating the social and emotional impacts of domestic violence. We draw on these advocates’ perspectives as experts in understanding disparities in mental health care and as guides in identifying spatially and culturally relevant interventions (see also McNichols, Witt, and Gatewood 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A significant amount of the existing research on competent mental health care in rural areas is focused on navigating community involvement and personal and professional boundaries (Breen & Drew, 2012; McNichols et al, 2016). However, research suggests that understanding rural culture and the unique concerns of residents in rural areas is also vital to engaging in competent practice in rural areas (Bischoff et al, 2014; Breen & Drew, 2012; McNichols et al, 2016). The history, geography, population, economics, and sociopolitical contexts of a rural area can influence perceptions of mental health and mental health services (Murray et al, 2004; Philo et al, 2003).…”
Section: Research Questionsmentioning
confidence: 99%